The Influence of Obesity and IL-6 on Infertile Iraqi Women with COVID-19 Complications (Baghdad Science Journal, 2023)
Infertility is one of the types of diseases that occur in the reproductive system. Obesity is a state that can be occurred due to excessive fats, the progression in obesity stage results in a change in adipose tissue and the development of chronic inflammation, endocrine glands disorders and women’s reproductive system, and also increase the infection with covid-19. The study aimed to investigate the effect of the obesity, lipid-profile, and IL-6 on hormones-dysregulation in infertile-women with COVID-19 complications. The current study included 70 samples: 50 infertility-women-with-covid-19-infected, 20 healthy-women/control, the ages of both patients and healthy subjects were selected within the range 18-34 years. Levels of FBS, LH, FSH, and testosterone and lipid profile were measured in addition to calculating BMI. The result showed a significant increase in lipid profile but no HDL that revealed a considerable decline in its level (P=0.001) in patients group relative to control group. Also, the results showed highly increase in LH and LH/FSH-ratio (p≤0.05(but no FSH that revealed a considerable decline in its level (p≤0.05). The results also showed that the values of IL-6 (7.46±1.90 ng/ml) and BMI (30.10 ±6.17 kg/m2) in the patients group were significantly higher (P-value=0.001) than their values in the control group (3.13±0.79), (22.09±2.63 kg/m2), respectively. Conclusion: Obesity and Corona-virus-infection negatively affect ovulation in infertile-women due to their effect on the pituitary-gland-hormones, in addition to causing chronic-infections that lead to an increase in the level of interleukin-6, which increases of pituitary gland disorder and the difficulty of treating infertility and increasing of corona complications.